2003
DOI: 10.1007/s00411-003-0214-7
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic radiation and cancer mortality among airline pilots: results from a European cohort study (ESCAPE)

Abstract: Cosmic radiation is an occupational risk factor for commercial aircrews. In this large European cohort study (ESCAPE) its association with cancer mortality was investigated on the basis of individual effective dose estimates for 19,184 male pilots. Mean annual doses were in the range of 2-5 mSv and cumulative lifetime doses did not exceed 80 mSv. All-cause and all-cancer mortality was low for all exposure categories. A significant negative risk trend for all-cause mortality was seen with increasing dose. Neith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 32 publications
4
45
0
4
Order By: Relevance
“…The results of these studies are not straightforward in interpretation since extraneous factors related to the unconventional lifestyle of air crews must be taken into account (Boice et al, 2000). Those large studies that have been reported recently Zeeb et al, 2003;Langner et al, 2004) have not found unexpected radiation-related risks. (It is of interest that enhanced levels of cosmic radiation are of particular concern for extended space flights, and considerable work has been carried out in assessing the doses likely to be received in a manned expedition to Mars (e.g.…”
Section: Introductionmentioning
confidence: 93%
“…The results of these studies are not straightforward in interpretation since extraneous factors related to the unconventional lifestyle of air crews must be taken into account (Boice et al, 2000). Those large studies that have been reported recently Zeeb et al, 2003;Langner et al, 2004) have not found unexpected radiation-related risks. (It is of interest that enhanced levels of cosmic radiation are of particular concern for extended space flights, and considerable work has been carried out in assessing the doses likely to be received in a manned expedition to Mars (e.g.…”
Section: Introductionmentioning
confidence: 93%
“…Among female flight attendants, seven studies found elevated risks of breast cancer, and six studies reported a higher than expected malignant melanoma risk (20,26). Airline personnel, however, differ from other shift workers both with respect to their occupational exposures to cosmic radiation (21) and their greater opportunity for recreational solar exposure. It is therefore difficult to know which factors are responsible for the observed excess cancer risks in this group of workers (20).…”
Section: Schwartzbaum Et Almentioning
confidence: 99%
“…In a meta-analysis of 13 studies of female breast cancer among night workers (including airline workers), Megdal et al (19) found an aggregate fixed-effects standardized incidence ratio (SIR) of 1.48 [95% incidence ratio (95% CI 1.36-1.61]. Excluding the seven studies of airline workers (who clearly differ from other shift workers because of their potential exposures to ionizing radiation (20,21) ), the aggregate SIR for the remaining six studies of shift workers was 1.51 (95% CI 1.36-1.68). However, the studies included in this metaanalysis have different definitions of exposure or varying exposure duration, and some findings are of borderline statistical significance.…”
mentioning
confidence: 99%
“…With regard to the key question of our paper, the latter investigations have provided direction for the former when cohort studies appeared to suggest a possibly higher breast cancer risk in female flight attendants. The seemingly likely culprit, cosmic radiation, was studied extensively (Langner et al 2004), but only in recent years have Mawson (1998) and Pukkala et al (2003) suggested that chronic interruptions in circadian rhythms or chronodisruption may be a possible explanation for moderately elevated breast and prostate cancer risks in some studies of female and male flight personnel, respectively. Only in recent years have experimental studies followed up on the initial observations in flight personnel and investigated the possible relationships between chronodisruption and the development of internal cancers in animals (Filipski et al 2004).…”
Section: Introductionmentioning
confidence: 99%